1998
DOI: 10.1111/j.1600-079x.1998.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo protection by melatonin against δ‐aminolevulinic acid‐induced oxidative damage and its antioxidant effect on the activity of haem enzymes

Abstract: Accumulation of delta-aminolevulinic acid (ALA), as it occurs in acute intermittent porphyria, is a potential endogenous source of reactive oxygen species (ROS) which can then produce oxidative damage to cell structures and macromolecules. This in vivo study investigated whether melatonin could prevent the deleterious effects of ALA. Rats were injected i.p. for 2 weeks with ALA (40 mg/kg on alternate days) and/or with melatonin (50 microg/kg or 500 microg/kg daily). Administration of pharmacological doses of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 42 publications
8
34
1
Order By: Relevance
“…The second effect is through the receptors over the genomes. Through these receptors, it induces enzymes that detoxify free radicals [10][11][12][13][14][15][16][17][18][19][20][21][22]. However, both the direct and indirect effects do not occur sufficiently at physiologic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The second effect is through the receptors over the genomes. Through these receptors, it induces enzymes that detoxify free radicals [10][11][12][13][14][15][16][17][18][19][20][21][22]. However, both the direct and indirect effects do not occur sufficiently at physiologic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous melatonin administration has been demonstrated to reduce the area occupied by intraluminal porphyrin accretions (Rodriguez-Colunga et al 1991) and the expression of the aminolevulinate synthase (the rate-limiting enzyme for porphyrin synthesis) gene and leads to decrease porphyrin concentrations (Dubey and Haldar 1997) in the rodent Harderian gland. Recently, Princ et al (1998) and Carneiro and Reiter (1998) have shown that, in the brain, melatonin prevents the damage induced by free radicals generated by porphyrin metabolism. Ultrastructural observations suggest that porphyrins in the rat Harderian gland are selectively secreted by the type II cells (Djeridane 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…In various experimental models of tissue damage, its protective role was reported by reducing oxidative stress and lipid peroxidation [6,7]. The ability of MEL to reduce radical production, increasing the activity of many antioxidant enzymes [8], has been demonstrated in oxidant-related pathological conditions, where radical species are measured in extracellular fluids [9,10]. …”
Section: Introductionmentioning
confidence: 99%